2019
DOI: 10.1371/journal.pone.0217615
|View full text |Cite
|
Sign up to set email alerts
|

Spatial spread of malaria and economic frontier expansion in the Brazilian Amazon

Abstract: The temporal and spatial evolution of malaria was described for the postfrontier phase of the Brazilian Amazon in 2003–2013. The current ecological study aimed to understand the relationship between spatial population mobility and the distribution of malaria cases. The study identified epidemiologically relevant areas using regional statistical modeling and spatial analyses that considered differential infections and types of work activities. Annual parasite incidence (API) in the region was highest in hotspot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 43 publications
(81 reference statements)
0
53
1
4
Order By: Relevance
“…In the Amazonian part of Brazil, between 2009 and 2015, each new square kilometer of deforestation was associated with 27 new cases of malaria [31]. A recent work that studied the spatial spread of malaria and "economic frontier" expansion in the Brazilian Amazon concluded that recent malaria cases were concentrated in the most remote areas characterized by economical projects including deforestation fronts [32]. In Colombia, the Annual Parasitic Incidence (API) for malaria was shown to increase according to the surface of illegally mined area [20,33].…”
Section: Deforestation and Number Of Malaria Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Amazonian part of Brazil, between 2009 and 2015, each new square kilometer of deforestation was associated with 27 new cases of malaria [31]. A recent work that studied the spatial spread of malaria and "economic frontier" expansion in the Brazilian Amazon concluded that recent malaria cases were concentrated in the most remote areas characterized by economical projects including deforestation fronts [32]. In Colombia, the Annual Parasitic Incidence (API) for malaria was shown to increase according to the surface of illegally mined area [20,33].…”
Section: Deforestation and Number Of Malaria Casesmentioning
confidence: 99%
“…A similar conclusion was found in Madre de Dios region in Peru in 2001-2012, where the number of malaria cases per month had a strong association with the amount of extracted gold, but a weak association with the average gold prices [13]. In Brazilian Amazon, the risk of malaria differs with the type of mining: the API in 2013 in municipalities with illegal mining activities was about 20.8 to 22.3, while that in areas with industrial legal mining was between 0.2 and 0.5 [32]. In Guyana, the number of malaria cases is correlated with gold price and therefore the extent of mining activities (unpublished data).…”
Section: Gold Production and Number Of Malaria Casesmentioning
confidence: 99%
“…Malaria burden in Brazil is concentrated in the Amazon Basin [2]. Within this region, transmission is spatially heterogeneous [3,4] with pockets of high malaria transmission associated with fish farming in rural and urban areas [5], arrival of susceptible individuals in new rural settlements in forest fringes, and illegal activities such as mining and logging [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Human movements, either seasonal or circular, or linear, within and across borders, are considered strong drivers of (re)introduction of malaria [13,15]. In the Amazon region, drivers of mobility include seasonal economic activities, seeking urban services, illegal activities, among others [4,16,7]. Commuting requires long hours in small boats or 4x4 vehicles to cross rivers or poorly maintained dirty roads.…”
Section: Introductionmentioning
confidence: 99%
“…commodities, among others [4,16,7]. Commuting requires long hours in small boats or 4x4 vehicles to cross rivers or poorly maintained dirty roads.…”
Section: Introductionmentioning
confidence: 99%